AUGUSTINE ONG RECEIVES NATIONAL ACADEMIC AWARD - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PUTRAJAYA, 23 September 2015 – Recipient of the Universiti Sains Malaysia (USM) Professor Emeritus in 2007, former Dean of the School of Chemical Sciences USM who is also a National Scientist, Professor Emeritus Tan Sri Datuk Dr. Augustine Ong Soon Hock received the National Academic Award (AAN), the nation’s highest accolade for academicians who excelled in the field of educational development.